Answer: q = 40
Step-by-step explanation:
Given the quadratic formula as
x = [-b +/-√(b^2 -4ac)]/2a
b = -14
a = 1
c = q
Difference d between the two roots.
d = [-b + √(b^2 -4ac)]/2a - [-b -√(b^2 -4ac)]/2a
d = 2√(b^2 -4ac)/2a
d = √(b^2 -4ac)/a
And d = 6
Substituting the values of a,b and c. We have;
6 = √[(-14^2) - (4×1×q)]
Square both sides
6^2 = 196 - 4q
4q = 196 - 36
q = 160/4
q = 40
The equation becomes
x^2 - 14x + 40 = 0
Simplifying
y = -25x + 200
Reorder the terms:
y = 200 + -25x
Solving
y = 200 + -25x
Solving for variable 'y'.
Move all terms containing y to the left, all other terms to the right.
Simplifying
y = 200 + -25x
When you multiply a whole number by a fraction, multiply the whole number by the numerator ( top number) and then divide by the denominator (bottom number).
8 x -8/9 = (8 *-8)/9 = -64/9 = -7 1/9 = -7.1